Caleidoscorpi: percepção, diferença e interação no design de mídias digitais - Silva, Daniele Fernandes da (2009)
This research has as aim to map/create sign qualities in digital medias in the web, specifically that can make its design becomes into a language capable to induce an aesthetical creation by emerging properties from its own qualities. We define design as desire (of continuity) that do not cease to establish perceptive and conceptual connections with the outside, the other, the caos and the web as a hypermedia, that makes possible the non-linear communication, always unconcluded and interactive. In the construction of this route, we meet the problematic itself, the being of what is not even thought (?-being, for Deleuze). However, we think and communicate by the language. According to peircean theory, perception presumes interaction between thought and outside. Then, interaction was thought as a method, extracted from the peircean theoretical support to connect distinct ways of existence. For Prigogine, complexity creation occurs by interaction between system and its entropic environment. Therefore, we proposed a dilation of present by construction of relations into an unconcluded environment as a basic condition to design creation in general, specifically in digital media, under the point of view of project. Thus, the theoretical study of difference, perception and interaction was made profound by mapping/creating conditions capable to provoke a creative process in design by digital media; this is the investigative importance of our research. Under the empiric point of view, we created a digital environment for real time design experimentation, expecting it can contribute to communication realm by distance education design